ANALYSIS AND INTERVENTION ON THE INFLUENCING FACTORS OF COLLEGE STUDENTS' PHYSICAL FITNESS - Bo,Peng (2021)
ABSTRACT Enhancing the physical health of college students is the fundamental guarantee of cultivating high-quality talents. In order to understand the influencing factors of college students' physical health and carry out targeted intervention, this study aims to analyze the factors affecting college students' physical health. Through the construction of physical health evaluation index and its influencing factors evaluation index, the importance of different indicators is evaluated by using the analytic hierarchy process, and a questionnaire about college students' physical health and its influencing factors is designed. The results show that the factors affecting college students' physical health include students' own factors, school factors, and others. At the same time, the insufficient construction of public sports facilities and the lack of first-class sports venues and equipment are also the reasons for the decline of college students' physique. Therefore, we can intervene in the students' physical health from the aspects of raising the students' awareness about physical exercise and Ensuring the construction of school sports facilities. It is hoped that this study can provide some reference for the empirical analysis and intervention research on the influencing factors of college students' physical health.